Epidemiological Evidence of Childhood Leukaemia around Nuclear Power Plants - Marek K. Janiak (SAGE Publishing, 2014)
A few reports of increased numbers of leukaemia cases (clusters) in children living in the vicinity of nuclear power plants (NPP) and other nuclear installations have triggered a heated debate over the possible causes of the disease. In this review the most important cases of childhood leukaemia clusters around NPPs are described and analyzed with special emphasis on the relationship between the environmental exposure to ionizing radiation and the risk of leukaemia. Since, as indicated, a lifetime residency in the proximity of an NPP does not pose any specific health risk to people and the emitted ionizing radiation is too small to cause cancer, a number of hypotheses have been proposed to explain the childhood leukaemia clusters. The most likely explanation for the clusters is 'population mixing', i.e., the influx of outside workers to rural regions where nuclear installations are being set up and where local people are not immune to pathogens brought along with the incomers.